2022
DOI: 10.1111/jfbc.14364
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of fortified yogurt with medicinal mushrooms from Phellinus species

Abstract: In light of the powerful therapeutic features of Phellinus species and due to the absence of toxic compounds, our investigations were aimed at screening of the antioxidant profile of fortified yogurts with hot water extracts from Phellinus torulosus and Phellinus igniarius leveled to 10%, 5%, and 1% final fortification concentrations after acknowledging their superior bioactive content and radical scavenging capacities (59.77% and 56.73% of DPPH inhibition, respectively) versus cold water extracts (29.87% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 85 publications
(95 reference statements)
3
5
0
Order By: Relevance
“…showing a positive effect on the antioxidant potency of dairy products which was consistent with previous reports (Dimitrova-Shumkovska et al, 2022). What is more, the TPC of all samples was significantly decreased during the storage, which might be due to the increased interactions between milk proteins and polyphenols (Kim et al, 2019) and the decomposition of polymeric phenolics in the presence of lactic acid bacteria during refrigerated storage (Hamed et al, 2021).…”
Section: Antioxidant Assayssupporting
confidence: 90%
See 2 more Smart Citations
“…showing a positive effect on the antioxidant potency of dairy products which was consistent with previous reports (Dimitrova-Shumkovska et al, 2022). What is more, the TPC of all samples was significantly decreased during the storage, which might be due to the increased interactions between milk proteins and polyphenols (Kim et al, 2019) and the decomposition of polymeric phenolics in the presence of lactic acid bacteria during refrigerated storage (Hamed et al, 2021).…”
Section: Antioxidant Assayssupporting
confidence: 90%
“…Interestingly, the syneresis was proteins and polyphenols during storage (Hamed et al, 2021) and thereby lowered syneresis. A similar decreasing pattern was also registered in the P. Igniarius and P. torulosus added yogurts during storage time of 14 days (Dimitrova-Shumkovska et al, 2022). These specific functional properties of LES may be useful for improving the syneresis of yogurt and deserves further study to explain it.…”
Section: The Structure and Rheological Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…The authors also claimed that the ethanol extract was the most pertinent for use as functional food (Kim et al, 2008). Jasmina Dimitrova-Shumkovska et al (2022) reported adding hot water extracted from Phellinus torulosus and Phellinus igniarius to yogurt products. The authors evaluated the above study has high applicability to create various functional foods appearing in Phellinus extract (Dimitrova-Shumkovska et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…( 2022 ) reported adding hot water extracted from Phellinus torulosus and Phellinus igniarius to yogurt products. The authors evaluated the above study has high applicability to create various functional foods appearing in Phellinus extract (Dimitrova‐Shumkovska et al., 2022 ). Meanwhile, the composition of higher fungi is influenced by various factors comprising climate change, ecological group conditions, and geographical area leading to the change in raw material quality (Vita et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%